Penguatan Variasi Produk Melalui Penerapan Teknologi Tepat Guna Pada Kampung Lemon Desa Eduwisata Sumberdem - Siti Ulfatul Faizah; Tisa Reta Vianda; Agung Winarno; Wening Patmi Rahayu (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service program aims to increase the business capacity of Kampung Lemon by strengthening marketing, product innovation, branding, and financial management. The main challenges faced include conventional marketing, limited product innovation, the lack of a visual product identity, and a manual financial recording system. The method used in this program is direct mentoring through training and practice for business owners. Activities include creating and managing digital marketing accounts through e-commerce platforms and social media, developing the